Process Development for Adoptive Cell Therapy in Academia: A Pipeline for Clinical-Scale Manufacturing of Multiple TCR-T Cell Products - Silva, Daniela Nascimento; Chrobok, Michael; Rovesti, Giulia; Healy, Katie; Wagner, Arnika Kathleen; Maravelia, Panagiota; Gatto, Francesca; Mazza, Massimiliano; Mazzotti, Lucia; Lohmann, Volker; Sällberg Chen, Margaret; Sällberg, Matti; et al. (Frontiers in Immunology, 2022)
Cellular immunotherapies based on T-cell receptor (TCR) transfer are promising approaches for treatment of cancer and chronic viral infections. The discovery of novel receptors is expanding considerably, however clinical development of TCR-T cell therapies still lags. Here we provide a pipeline for process development and clinical-scale manufacturing of TCR-T cells in academia. We utilized two TCRs specific for Hepatitis C virus as model, because of their marked differences in avidity and functional profile in TCR-redirected cells. With our clinical scale pipeline, we reproduced the functional profile associated with each TCR; moreover, the two TCR-T cell products demonstrated similar yield, purity, transduction efficiency as well as phenotype. The TCR-T cell products had a highly reproducible yield of over 1.4x109 cells, with an average viability of 93%; 97.8-99% of cells were CD3+, of which 47.662.02% were CD8+ T cells; the phenotype was markedly associated with central memory (CD62L+CD45RO+) for CD4+ (93.705,23%) and CD8+ (94.264.04%). Functional assessments in 2D and 3D cell-culture assays showed that TCR-T cells mounted a polyfunctional response to the cognate HCV-peptide target in tumor cell lines, including killing. Collectively, we report a solid strategy for efficient large-scale manufacturing of TCR-T cells.